2020
DOI: 10.5144/0256-4947.2020.126
|View full text |Cite
|
Sign up to set email alerts
|

Gingival health and oral hygiene practices among high school children in Saudi Arabia

Abstract: BACKGROUND: Gingivitis is a site-specific inflammatory condition initiated by dental biofilm accumulation. The accumulation of dental plaque on the gingival margin triggers inflammatory effects that can become chronic. In addition to its local effect, gingival inflammation has recently been suggested to have an impact on general health. OBJECTIVE: Determine the prevalence of gingivitis and its relationship to oral hygiene practices in high school children in Saudi Arabia. DESIGN: Cross-sectional. SETTING: High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
14
0
4
Order By: Relevance
“…27 Children in the country also demonstrate poor oral hygiene, accumulation of dental plaque, and gingivitis. 19,28 Dental caries and other dental diseases if left untreated can exacerbate oral problems and development of dental pain. Therefore, the high prevalence of oral diseases in children may explain the reasons behind increased dental visits due to dental pain in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…27 Children in the country also demonstrate poor oral hygiene, accumulation of dental plaque, and gingivitis. 19,28 Dental caries and other dental diseases if left untreated can exacerbate oral problems and development of dental pain. Therefore, the high prevalence of oral diseases in children may explain the reasons behind increased dental visits due to dental pain in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Silveira et al, 2019),(AlGhamdi et al, 2020),(Breuer and Cosgrove, 1989) Disproportionate disparities by gender were found to exist with respect to demographics and behavioural predictors. Males are found to be associated with periodontal diseases because of their poor oral hygiene and females due to the estrogen levels.…”
mentioning
confidence: 93%
“…15 Tongue brushing is associated with an improvement in periodontal status. 16 and to controlling halitosis in children. 17 Scraping and brushing the tongue have shown to reduce the counts of salivary Streptococcus mutans in children.…”
Section: Introductionmentioning
confidence: 99%
“…17 Scraping and brushing the tongue have shown to reduce the counts of salivary Streptococcus mutans in children. [15][16][17][18] There is no high-quality evidence regarding postbrushing rinsing. 19 Clinical guidelines for children recommend spitting out the excess of toothpaste and not rinsing with water after brushing.…”
Section: Introductionmentioning
confidence: 99%